2011
DOI: 10.1089/vbz.2010.0195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Three ZoonoticBabesiaSpecies inIxodes ricinus(Linné, 1758) Nymphs in a Suburban Forest in Switzerland

Abstract: The tick Ixodes ricinus (Linné, 1758) is known as the vector of various Babesia spp. pathogenic for humans. In Switzerland, three of them, Babesia divergens, Babesia venatorum (also known as Babesia EU1), and Babesia microti, have been reported in I. ricinus ticks from various areas. The aim here was to determine how frequently these species infect I. ricinus nymphs in a suburban forest and to determine their prevalence over 3 years along a pathway delimited in four different sections. Babesia spp. was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Co-infections of unrelated human pathogens have been documented for Ixodes species (Tokarz et. al., 2010; Burri et al, 2011; Gigandet et al, 2011) and P. leucopus (Anderson et al, 1986; Johnson et al, 2011). Therefore, frequent feedings by infected ticks on white-footed mice would tend to elevate antibody titers and antibody prevalences during summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infections of unrelated human pathogens have been documented for Ixodes species (Tokarz et. al., 2010; Burri et al, 2011; Gigandet et al, 2011) and P. leucopus (Anderson et al, 1986; Johnson et al, 2011). Therefore, frequent feedings by infected ticks on white-footed mice would tend to elevate antibody titers and antibody prevalences during summer.…”
Section: Discussionmentioning
confidence: 99%
“…A review of medical records for elderly persons revealed relatively high babesiosis rates for Connecticut, Rhode Island, New York, and Massachusetts and possible presence of this disease in other eastern states (Menis et al, 2012). Moreover, B. microti coexists with Babesia divergens or Babesia venatorum (also known as Babesia EU1 ) in Europe (Gigandet et al, 2011; Lempereur et al, 2011). Therefore, in the Holarctic where Ixodes species exist and different strains or genospecies of B. burgdorferi sensu lato and A. phagocytophilum likewise occur, B. microti should be considered in ecologic and epidemiologic studies as well as in the differential diagnosis of unknown febrile human illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…One such emerging pathogen is Babesia , a parasite first detected in cattle but now a well-known cause of malaria-like illness in humans [ 1 - 3 ]. Newly recognized endemic foci for human babesiosis include Europe [ 4 ] where Ixodes ricinus, a vector of multiple species of Babesia, is common. Apparently the most common tick in Europe [ 5 ], I. ricinus has a world-wide occurrence and low host specificity, parasitising on a variety of larger mammals, including humans [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, B. divergens –like organisms have been reported in Kentucky, Missouri, and Washington State [4]. In Europe, almost all reported cases have been due to B. divergens , and a few have been caused by the EU1 species, now called B. venatorum [5], [6]. Sporadic cases of babesiosis have also been reported in Asia, Africa, Australia, and South America [7].…”
Section: What Is Babesiosis?mentioning
confidence: 99%